Advanced dynamics : Analytical and numerical calculations with MATLAB - Marghitu, Dan B. (Springer New York, 2012)
Advanced Dynamics: Analytical and Numerical Calculations with MATLAB provides a thorough, rigorous presentation of kinematics and dynamics while using MATLAB as an integrated tool to solve problems. Topics presented are explained thoroughly and directly, allowing fundamental principles to emerge through applications from areas such as multibody systems, robotics, spacecraft and design of complex mechanical devices. This book differs from others in that it uses symbolic MATLAB for both theory and applications. Special attention is given to solutions that are solved analytically and numerically using MATLAB. The illustrations and figures generated with MATLAB reinforce visual learning while an abundance of examples offer additional support. This book also: Provides solutions analytically and numerically using MATLAB Illustrations and graphs generated with MATLAB reinforce visual learning for students as they study Covers modern technical advancements in areas like multibody systems, robotics, spacecraft and design of complex mechanicaldevices and mechanisms Includes comprehensive MATLAB programs for the example problems Advanced Dynamics: Analytical and Numerical Calculations with MATLAB is an ideal book for senior undergraduate and first year graduate students in mechanical engineering.